15.33 Phenotype-genotype characterisation of 'long survivors' with motor neurone disease in Scotland. Issue 12 (14th November 2019) - Leighton, Danielle; Newton, Judith; Parry, David; Colville, Shuna; Swingler, Robert; Porteous, Mary; Aitman, Tim; Gorrie, George; Chandran, Siddharthan; Pal, Suvankar
Abstract : The Clinical Audit Research and Evaluation of Motor Neurone Disease (CARE-MND) platform has collected information from people with MND in Scotland since 1989. In a recent analysis, upper range of survival from diagnosis was 25.8 years. We investigated phenotypes and genotypes of a 'long-surviving' cohort (>8 years from diagnosis). 14 phenotypic variables were analysed, and compared with unselected incident patients. DNA samples underwent whole genome sequencing and screening for C9orf72 expansions. 60 long survivors were identified. 46 were alive at censorship, giving a Scottish prevalence of 11.0%. Long survivors were younger than incident patients (p<0.0001) and tended to have lower limb-onset disease (p=0.003). Disease classification differed (p<0.0001); 41.7% had primary lateral sclerosis (PLS). 7/34 (20.6%) had pathogenic/likely-pathogenic mutations. Four had SOD1 mutations; three the Scottish p.I114T founder mutation. Remaining patients had variants in FUS, ALS2 and SPG11. The individual with the SPG11 variant also had a variant of uncertain significance in the same gene. Long survivors in the Scottish MND population are younger, and have increased prevalence of PLS and lower limb-onset disease. SOD1 p.I114T variant can result in long survival. Compound heterozygosity in SPG11 may be associated with MND. Diagnostic genotyping should be considered in long duration of disease.